Corporate Social Responsibility (CSR) dan Good Corporate Governance (GCG) Terhadap Nilai Perusahaan Sektor Pertambangan - Lestari, Endang; Yuliawati, Yuliawati; Amrina, Dania Hellin (IJMA (Indonesian Journal of Management and Accounting), 2023)
Business activities that are in direct contact with the utilization of natural resources certainly have a direct impact on the environment so there is a need for a system that can provide direction and control so that companies carry out and disclose their social responsibility activities transparently. The company's consideration of the costs incurred to implement Corporate Social Responsibility (CSR) indicates that the company still prioritizes the financial side compared to the non-financial side. This research aims to determine the effect of CSR and Good Corporate Governance (GCG) wich is proxied with Independent Board of Commissioners, Managerial Ownership, Institutional Ownership and Audit Committee on the Value of Companies listed on the Indonesian Sharia Stock Index (ISSI) in the mining sector in 2015-2020. The method used is purposive sampling method while the population of this study is mining companies listed on the ISSI. Sampling using purposive sampling obtained a sample of 48 samples. This study uses secondary data obtained from the company's annual financial reports published on the internet through the official website of the Indonesia Stock Exchange www.idx.co.id and from the official website of each company. The results of the study: (1) CSR has a significant effect on firm value (2) Independent Board of Commissioner has no significant effect on firm value (3) Managerial Ownership has a significant effect on firm value (4) Institutional Ownership has a significant effect on firm value (5) audit committee has no significant effect on firm value.